Procedural Safety and Device Performance of the Portico™ Valve from Experienced TAVI Centers: 30-Day Outcomes in the Multicenter CONFIDENCE Registry - Mollmann, Helge; Linke, Axel; Nombela-Franco, Luis; Sluka, Martin; Dominguez, Juan Francisco Oteo; Montorfano, Matteo; Kim, Won-Keun; Arnold, Martin; Vasa-Nicotera, Mariuca; Conradi, Lenard; Camuglia, Anthony; Bedogni, Francesco; et al. (Journal of clinical medicine, 2022)
A total of 1001 subjects (82.0 years, 62.5% female, 63.7% NYHA III/IV at baseline) with severe aortic stenosis at high surgical risk were enrolled in the prospective CONFIDENCE registry and treated with a Portico™ transcatheter heart valve (THV) using either a first-generation delivery system (DS) or the FlexNav™ DS. The objective of this registry is to characterize the procedural safety and device performance of the Portico™ THV at 30 days. The study collected ‘standard-of-care’ clinical and device performance data, with adverse events adjudicated by an independent clinical event committee according to the Valve Academic Research Consortium-2 criteria. The implantation of a single Portico™ THV was successful in 97.5% of subjects. The 30-day all-cause mortality, cardiovascular mortality, and disabling stroke rates were 2.6%, 2.1%, and 1.8%, respectively. A new pacemaker was implanted in 19.0% of subjects at 30 days. At 30 days, the effective orifice area and mean gradient values were 1.82 cm2 and 7.1 mmHg, respectively. The 30-day rate of moderate paravalvular leak (PVL) was 2.1%, with no occurrence of severe PVL. The Portico™ THV demonstrated improved hemodynamic performance and low rates of safety events at 30 days in a large cohort of subjects implanted with the Portico™ THV with either the first-generation DS or FlexNav™ DS.